Carbon dioxide storage in functional porous adsorbents for various operating conditions - Chan, Jax (Nanyang Technological University, 2023)
The key technology for reducing the greenhouse gas emissions generally deals with the capture and storage of carbon dioxide (CO2) from flue gases, waste heat source and the building envelope. The functional porous adsorbents such as activated carbons, fibres, zeolites, metal-organic frameworks (MOFs) etc. are one favourable strategy as they can selectively adsorb and separate CO2 gas from other gases. However, research activities on CO2 capture, storage and utilization are in advanced stages. The adsorption-based CO2 storage and the development of functional porous adsorbents are important research areas. The report begins with the description of from the functional adsorbent’s synthesisation and characterisation. The metal-organic frameworks (MOFs) namely parent HKUST-1, and modified HKUST-1:BMlMCl(1/2) and HKUST-1:BMlMCl(1) are synthesized by hydrothermal reaction methods. The surface characteristics were performed by SEM (scanning electron micrography), CO2 adsorption (for pore size distribution) and thermogravimetric analyser (for measuring thermal stability). The CO2 adsorption uptakes on these functional materials are measured by a volumetric apparatus. The CO2 uptakes are evaluated for various temperatures and the pressures up to 6 bar. These results are presented in the form of isotherms, which are required to understand the charging of CO2 gas molecules for a given pressure and temperature. All these experimental data are furnished in this report with future research directions.